The Role of Ultrasound Simulation in Obstetrics and Gynecology Training: A UK Trainees' Perspective. Issue 5 (October 2016) - Patel, Hersha; Chandrasekaran, Dhivya; Myriokefalitaki, Eva; Gebeh, Alpha; Jones, Kate; Jeve, Yadava B
Abstract : Introduction: Ultrasonography is a core skill required by all obstetrics and gynecology trainees; however, training opportunities in clinical ultrasound are declining. Simulation ultrasound training has been proposed as a strategy to overcome this. The study aims were to determine the current availability of clinical and simulation ultrasound training in obstetrics and gynecology in the United Kingdom and to explore the trainees' perspective on the role of ultrasound simulation. Methods: All obstetrics and gynecology trainees within the East Midlands Local Education Training Board in the United Kingdom were asked to complete an anonymous web-based survey in July 2014. Results: Of 140 trainees, 70 (50%) responded to the survey, and 69% reported rarely having dedicated clinical ultrasound sessions. Fifty percent had failed to achieve ultrasound competencies required for their stage of training, and 83% felt that the pressures of service provision limited their exposure to clinical ultrasound. Seventy-three percent of the trainees considered ultrasound simulation to be an essential component of training, and 69% agreed that it would help improve their clinical skills. Only 50% had access to an ultrasound simulator. Seventy-seven percent of the trainees thought that it would be useful to have ultrasound simulation integrated into training. Conclusions: Trainees are struggling to achieve minimal ultrasound competences with clinical ultrasound training alone. They believe that ultrasound simulation will shorten the learning curve and improve their clinical skills and knowledge. Despite the cost implications of simulation training, we propose that consideration is given to formal integration of ultrasound simulation into the curriculum as a possible way forward.